2022
DOI: 10.3390/chemosensors10070244
|View full text |Cite
|
Sign up to set email alerts
|

E-Senses, Panel Tests and Wearable Sensors: A Teamwork for Food Quality Assessment and Prediction of Consumer’s Choices

Abstract: At present, food quality is of utmost importance, not only to comply with commercial regulations, but also to meet the expectations of consumers; this aspect includes sensory features capable of triggering emotions through the citizen’s perception. To date, key parameters for food quality assessment have been sought through analytical methods alone or in combination with a panel test, but the evaluation of panelists’ reactions via psychophysiological markers is now becoming increasingly popular. As such, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 137 publications
0
13
0
Order By: Relevance
“…In more depth, this approach is deemed particularly useful in the food and drink industry, where the inter-connection between panel questionnaires, chemical sensors, and derived devices (e.g., e-Nose, e-Tongue, e-Eye)—with the study of emotions of panelists and consumers at large—is becoming key, as has been suggested [ 6 ]. At the same time, the interaction usually performed by a panelist or a consumer at large with a given edible compound (either food or beverage) should not be significantly altered by the application of a monitoring tool or by the use of gold standard, complex, wired instrumentation that is poorly feasible in the specific framework.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In more depth, this approach is deemed particularly useful in the food and drink industry, where the inter-connection between panel questionnaires, chemical sensors, and derived devices (e.g., e-Nose, e-Tongue, e-Eye)—with the study of emotions of panelists and consumers at large—is becoming key, as has been suggested [ 6 ]. At the same time, the interaction usually performed by a panelist or a consumer at large with a given edible compound (either food or beverage) should not be significantly altered by the application of a monitoring tool or by the use of gold standard, complex, wired instrumentation that is poorly feasible in the specific framework.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the decisions taken by consumers rely on the information projected from the environment into their human body. In such a framework, food scientists might not consider the influence of thinking processes on sensory assessment, mainly focusing on stimulus-dependent techniques (the so-called “bottom-up approach”), including scaling or triangle tests for evaluating smell, taste, and flavor [ 6 , 7 ]. Overall, this approach is mainly used when attempting to define the main sensory features of an edible compound for a precise group (e.g., a cohort characterized by a given culture or age).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, the determination of food quality is of considerable importance, not only to comply with commercial regulations but also to meet consumer expectations [1] . Nutritional, microbiological, and physicochemical properties are all important parameters when determining food quality.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, novel methods, including electronic tongue and electronic nose (e-senses), have become an essential focus of researchers and many industries because they can serve as alternative methods to human sensory testing. This is because these e-senses can overcome the problems of sensory methods using human sensory panels, including subjectivity, panelists’ sensory fatigue, high expenses, and a more time-consuming method ( Modesti et al, 2022 ). Furthermore, these e-senses can be considered fast and valid alternative instruments compared to other analytical techniques, including spectroscopy, which are very sensitive, selective, and expensive, with needed pretreatment steps for sample preparation.…”
Section: Introductionmentioning
confidence: 99%